Athenar bermani, a new species of dicraeosaurid sauropod from Dinosaur National Monument, Utah, U.S.A. - Whitlock, John A. (2025)
Carnegie Museum of Natural History houses some of the most important specimens for our understanding of diplodocoid sauropod cranial anatomy. One specimen(CM 26552), a braincase and partial skull roof, is often overlooked in favor of morecomplete skulls, but bears an outsized historical importance as this specimen formedthe basis for the modern description of braincase anatomy for Diplodocus as a genus.In light of several decades of new discoveries since the original description by Bermanand McIntosh in 1978, here we re-evaluate the anatomy and taxonomic relationships ofthis specimen. We find that CM 26552 is a distinct not only from Diplodocus but alsofrom the larger grouping Diplodocidae entirely, and is instead best regarded as a newgenus of dicraeosaurid sauropod.